The cGAS-STING signaling pathway: emerging targets and challenges in breast cancer immunotherapy - Sun, Lei; Chen, Jing; Zeng, Shiyan (Frontiers in Immunology, 2026)
The cGAS-STING signaling pathway serves as a crucial bridge between innate and adaptive immunity, playing a dual role in breast cancer pathogenesis and treatment. This review delves into its complex functions within the breast tumor microenvironment, where pathway activation can either stimulate potent antitumor immunity or paradoxically promote tumor progression through immunosuppressive mechanisms. We examine the promising therapeutic strategy of utilizing STING agonists to transform immunologically quiescent tumors into T-cell-inflamed environments and their synergistic potential when combined with established modalities. The translation of these findings into clinical practice, however, faces considerable hurdles. This work critically summarizes the overarching challenges in the field and explores innovative approaches designed to overcome them. Finally, we present a forward-looking perspective on the rational development of next-generation immunotherapies centered on cGAS-STING pathway modulation, outlining key priorities for achieving its full therapeutic potential in breast cancer.